Economic modelling and analysis of Hungarian wheat production in the marketing year 2011 - Kiss, István (Applied Studies in Agribusiness and Commerce, 2012)
In the framework of the present study I analysed the wheat production sector. In order to evaluate the situation prevailing in the sector I conducted an economic analysis which I based on primary data collection. The year of investigation was the production year of 2011. Long-term implications for different crop sectors can only be based on multi-annual analysis, so in this article I only attempted to analyse the sector with respect to 2011. To evaluate wheat production I compiled its cost structure and assessed it. To evaluate its position in comparison to other crops I also carried out calculations to determine the gross margin (revenue minus variable cost)1 By gross margin I mean the gross margin (C), which is production value (PV) minus direct cost (DC), by definition (C=P-DC). of maize and rape. I observed that the gross margin attainable on one hectare was the lowest in the case of wheat. I applied two types of gross margin, because I consider it important that a given sector should also be profitable without subsidies. In the case of the gross margin including subsidies it is essential to emphasize the role of subsidies, since their ratio varied between 30 and 47% of the total revenue. The importance of subsidies was the most significant in the case of winter wheat.